Conductive porous material, electrode using same, and method for producing conductive porous material
By using biologically sourced fibrous carbon sources to coexist with graphene in the manufacturing of graphene electrode materials, and through physical peeling and high-temperature sintering technology, the recondensation of graphene is inhibited, and the safety and recondensation of oxidation treatment are solved, achieving the goal of achieving Efficient and low-cost conductive porous materials are prepared, and the electrode performance is improved.
Patent Information
- Application Number
- CN202380041642.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-08
- Filing Date
- 2023-04-25
- Publication Date
- 2024-12-31
AI Technical Summary
During the manufacturing process of the existing graphene electrode materials, potassium permanganate and concentrated sulfuric acid are used in the oxidation treatment, resulting in high manufacturing cost and safety hazards. At the same time, the recondensation problem of graphene leads to a decrease in specific surface area and a decrease in dispersion, which affects the electrode performance. .
A biologically sourced fibrous carbon source coexisted with graphene, a dispersion was prepared by physical peeling treatment, and sintered at high temperature to form a carbon skeleton structure, inhibiting the recondensation of graphene and improving dispersion and specific surface area.
The preparation of conductive porous materials with high dispersion and high specific surface area is achieved, which reduces production costs and improves the performance and safety of electrode materials. It is suitable for lithium-ion batteries, electric double layer capacitors and other equipment.
Smart Images

Figure CN119234280A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive porous material, an electrode using the conductive porous material, and a method for producing the conductive porous material. Background Art
[0002] In order to realize a decarbonized society, there is a strong demand for improving the performance of power storage devices such as lithium-ion batteries and double-layer capacitors, and power generation devices such as fuel cells and solar cells. In any device, improving electrode materials is effective as a method for improving performance. In order to improve the electrical properties of electrode materials, it is important to improve the conductivity of electrode materials and increase the specific surface area of electrode materials.
[0003] Graphene has a surface area of up to 2630 m 2 / g and high conductivity, it has attracted attention as a new electrode material to replace the current activated carbon electrode (non-patent literature 1, 2). For example, the capacitance of chemically modified graphene (CMG) was 135F / g when measured in an aqueous electrolyte and 99F / g in an organic electrolyte (non-patent literature 2), which is more than three times higher than the capacitance of an activated carbon electrode (about 30 to 40F / g).
[0004] As a method for producing an electrode material containing graphene, there is a method of oxidizing graphite to produce graphite oxide, dispersing graphite oxide in a solvent and then exfoliating it in layers to obtain graphene oxide (Patent Document 1, Non-Patent Documents 2 to 4). After the graphene oxide is formed into a desired shape such as a film, the graphene oxide is reduced to obtain an electrode material containing graphene.
[0005] In the oxidation treatment of graphite, a strong oxidizing agent such as potassium permanganate and concentrated sulfuric acid are used (Patent Document 1, Non-Patent Document 2).
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2012-31024
[0009] Non-patent literature
[0010] Non-patent literature 1: Xia jL, et al., Nat. Nanotechnol., 4 (2009) 505-509.
[0011] Non-patent document 2: Stoller MD, et al., Nano Lett., 8 (2008) 3498-3502.
[0012] Non-patent document 3: Hummers WS, et al., J. Am. Chem. Soc., 80 (1958) 1339.
[0013] Non-patent document 4: Wen Z., et al., Adv. Mater., 24 (2012) 5610-5616. Summary of the invention
[0014] An electrically conductive porous material according to one embodiment of the present invention is the following electrically conductive porous material:
[0015] It contains a skeleton structure containing fibrous carbon of biological origin and graphene held by the skeleton structure.
[0016] The volume resistivity measured under a pressure of 10 MPa or less is 1.0×10 -3 ~1.0×10 0 Ω·cm,
[0017] The biomass degree measured by accelerator mass spectrometry (AMS) was in the range of 5 to 55 pMC. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1A This is a schematic diagram for explaining a method for producing a conductive porous material according to an embodiment of the present invention.
[0019] Figure 1B This is a schematic diagram for explaining a method for producing a conductive porous material according to an embodiment of the present invention.
[0020] Figure 1C This is a schematic diagram for explaining a method for producing a conductive porous material according to an embodiment of the present invention.
[0021] Figure 1D This is a schematic diagram for explaining a method for producing a conductive porous material according to an embodiment of the present invention.
[0022] Figure 2 This is a photograph of the appearance of the conductive porous material of Example 1.
[0023] Figure 3 is a SEM image of the conductive porous material of Example 1.
[0024] Figure 4 This is a SEM image of the conductive porous material of Example 2.
[0025] Figure 5 This is a SEM image of the conductive porous material of Example 3.
[0026] Figure 6This is a SEM image of the conductive porous material of Example 4.
[0027] Figure 7 This is a SEM image of the conductive porous material of Example 5.
[0028] Figure 8 This is a SEM image of the conductive porous material of Example 6.
[0029] Fig. 9 This is a SEM image of the conductive porous material of Example 7.
[0030] Fig.10 This is a photograph of the appearance of the graphite powder of Comparative Example 1.
[0031] Fig.11 This is a SEM image of the graphite powder of Comparative Example 1.
[0032] Fig.12 This is a graph showing the pressure dependence of the volume resistivity of the conductive porous material.
[0033] Fig.13 This is a graph showing the relationship between the cellulose nanofiber weight ratio of the conductive porous material (before calcination) and the biomass degree of the conductive porous material (calcined body). DETAILED DESCRIPTION
[0034] Graphene with a flat scale shape is easy to stack and condense due to van der Waals force. For example, even if graphene is forcibly dispersed in a dispersion medium, it is easy to re-condense. Therefore, when the specific surface area of an electrode material containing graphene is actually measured, it may be significantly lower than the theoretical value.
[0035] When graphene oxide as disclosed in Patent Document 1 and Non-Patent Documents 2 to 4 is used to produce an electrode material, graphene oxide has a large number of oxygen functional groups such as hydroxyl groups and carboxyl groups on its surface, so it has excellent dispersibility in a dispersion medium. However, since graphene oxide is finally reduced to remove oxygen functional groups, the reduced graphene re-agglomerates, and the specific surface area is still reduced.
[0036] Therefore, when forming an electrode material using graphene, it is important to suppress the re-aggregation of graphene.
[0037] In addition, since poisons such as potassium permanganate and concentrated sulfuric acid are used in the oxidation treatment for obtaining graphene oxide, the production cost of graphene becomes high, and it may be dangerous when mass-produced. Therefore, a new method for producing an electrode material containing graphene without performing an oxidation treatment is required.
[0038] In a method of obtaining a graphene dispersion by physically exfoliating a graphene source such as graphite under wet conditions, as the graphite is exfoliated and graphene is generated, the specific surface area of the graphene increases and the dispersion thickens rapidly, thereby reducing the exfoliation efficiency of the graphite and the dispersibility of the graphene in the dispersion.
[0039] The inventors of the present invention have found that by adding a biologically derived fibrous carbon source (biomass fiber) to a graphene dispersion in advance so that the fibrous carbon source and graphene coexist, the interaction between graphenes can be reduced. The use of the fibrous carbon source can suppress the thickening of the graphene dispersion and obtain a graphene dispersion with high dispersibility.
[0040] By calcining the composite obtained by drying the dispersion at a high temperature to carbonize the fibrous carbon source, a skeleton structure containing fibrous carbon can be formed. In addition, a conductive porous material in which graphene is retained in the skeleton structure can be obtained.
[0041] In addition, in a method for manufacturing a conductive porous material in one embodiment of the present invention, when preparing a graphene dispersion, energy is applied from the outside to a mixed solution obtained by mixing a graphene source, a dispersion medium, and a fibrous carbon source of biological origin. Thus, the graphene source is physically stripped to generate graphene. Since graphene is stable in contact with a fibrous carbon source, the dispersion state of graphene is maintained and re-agglomeration is suppressed. In this way, a graphene dispersion with excellent dispersibility can be obtained.
[0042] According to the method for producing a conductive porous material according to one embodiment of the present invention, since it is not necessary to chemically treat a graphene source, the production efficiency is high and the utilization value is also high in industry.
[0043] It should be noted that although the graphene production process based on the chemical vapor deposition (CVD) method does not require oxidation treatment of graphene, the productivity of graphene is low and the production cost is high.
[0044] An object of the present invention is to provide a conductive porous material in which re-aggregation of graphene is suppressed, and an electrode including the conductive porous material.
[0045] Another object of the present invention is to provide a method for producing the conductive porous material of the present invention without performing an oxidation treatment on graphene.
[0046] A first aspect of the present invention is a conductive porous material,
[0047] It contains a skeleton structure containing fibrous carbon of biological origin and graphene held by the skeleton structure.
[0048] The volume resistivity measured under a pressure of 10 MPa or less is 1.0×10 -3 ~1.0×10 0 Ω·cm,
[0049] The biomass content measured by accelerator mass spectrometry (AMS) was in the range of 5 to 55 pMC.
[0050] A second aspect of the present invention is the conductive porous material according to the first aspect, wherein:
[0051] In the above-mentioned skeleton structure, 80 atomic % or more of the entire skeleton structure is carbon atoms.
[0052] A third aspect of the present invention is the conductive porous material according to the following aspect 1 or 2, wherein:
[0053] The skeleton structure includes a calcined product obtained by calcining one or more fibrous carbon sources selected from the group consisting of cellulose, chitin, chitosan, lignin, and tannic acid.
[0054] A fourth aspect of the present invention is an electrode including the conductive porous material according to any one of aspects 1 to 3.
[0055] A fifth aspect of the present invention is a method for producing a conductive porous material, the method for producing the conductive porous material according to any one of aspects 1 to 3 comprising:
[0056] (1) a step of mixing a dispersion medium, a graphene source, and a biogenic fibrous carbon source and applying external energy to prepare a dispersion liquid containing the dispersion medium, the graphene, and the fibrous carbon source;
[0057] (2) a step of removing the dispersion medium from the dispersion liquid to produce a composite body including graphene and the fibrous carbon source; and
[0058] (3) A step of firing the composite to obtain a conductive porous material.
[0059] A sixth aspect of the present invention is the method for producing a conductive porous material according to the fifth aspect, wherein:
[0060] The fibrous carbon source is one or more selected from the group consisting of cellulose, chitin, chitosan, lignin, and tannic acid.
[0061] A seventh aspect of the present invention is the method for producing a conductive porous material according to the following aspect 5 or 6, wherein:
[0062] The graphene source is at least one selected from artificial graphite, natural graphite and multilayer graphene.
[0063] An eighth aspect of the present invention is the method for producing a conductive porous material according to any one of the following aspects 5 to 7, wherein:
[0064] The above dispersion medium is water.
[0065] According to one embodiment of the present invention, a conductive porous material in which re-aggregation of graphene is suppressed and an electrode including the conductive porous material can be provided.
[0066] According to another embodiment of the present invention, a method for producing a conductive porous material without performing an oxidation treatment on graphene can be provided.
[0067] Hereinafter, the present embodiment will be described by giving examples of preferred embodiments of the invention.
[0068] <Conductive porous materials>
[0069] The conductive porous material of the embodiment of the present invention includes a skeleton structure of fibrous carbonaceous material of biological origin and graphene held by the skeleton structure. The skeleton structure can suppress the aggregation of graphene. Therefore, a conductive porous material with a large specific surface area can be obtained.
[0070] Radiocarbon 14 C measurement was used to confirm that the fibrous carbon contained in the skeleton structure was of biological origin. 14 C can be analyzed, for example, by using accelerator mass spectrometry (AMS). 14 Since the AMS method can directly measure the decay of C in the sample, the measurement can be completed in a short time, and the measurement can be completed in about 1 hour for each sample. 14 Since the amount of C can be measured, the amount can be measured at about one thousandth of the amount of sample used in the β-ray counting method. The AMS method can measure samples that could only be collected in very small quantities in the past, precious cultural relics, and other samples that were intended to be destroyed to the minimum, and the AMS method is effectively used in various fields.
[0071] 14 One of the characteristics of C is that it is a radioactive isotope that decays radioactively into nitrogen with a half-life of 5730 years. 14 On Earth, extremely small amounts of 14 C. Generated 14 C is oxidized to carbon dioxide 14CO2 diffuses into the atmosphere and is taken into animals and plants in the food chain. It circulates in the environment through the food chain and disappears with its half-life. This phenomenon is used to carry out dating. On the other hand, human activities after the Industrial Revolution have had an impact on nature. 14 C cycle brings changes. Not included 14 The use of fossil fuels such as oil and coal (called dead C) has led to the apparent 14 On the other hand, the concentration of C decreased, and the nuclear tests in the atmosphere were carried out for about 10 years from the 1950s. 14 The generation of C (Bomb C) in the atmosphere 14 The concentration of C has increased dramatically. Therefore, the carbon from organisms that have existed since 1950 is called modern C, which contains thousands of times more C than fossil fuels. 14 C.
[0072] Modern carbon of biological origin is thought to have about 1.2 × 10 -12 of 14 C / 12 C ratio, the dead C of fossil fuel sources has a carbon content of 1.0×10 -16 The following 14 C / 12 C ratio. By utilizing this knowledge, it is possible to determine whether the fibrous carbonaceous material contained in the skeleton structure is of biological origin.
[0073] (Biomassness of Conductive Porous Materials)
[0074] The content of biological resources (biomass) in the test sample can be expressed as an index called "biomass degree". Biomass degree is specified in ASTM D6866-22 and can be expressed based on the amount of carbon ( 14 The unit of biomass is pMC (percent Modern Carbon). When the sample is made of 100% biological materials, the biomass is about 100 pMC, and when it is made of 100% fossil fuel materials, the biomass is about 0 pMC.
[0075] If the fibrous carbonaceous material constituting the conductive porous material is of biological origin, the radioactive carbon in the conductive porous material can be measured by using the aforementioned AMS method. 14 The biomass degree of the conductive porous material can be determined by measuring the concentration of carbon. In this way, the concentration of biogenic carbon contained in the conductive porous material can be quantified.
[0076] When the biomass degree of the conductive porous material is measured by the AMS method, it is preferably 5 to 55 pMC, and more preferably 10 to 30 pMC.
[0077] (Volume resistivity of conductive porous materials)
[0078] Since the volume resistivity of the conductive porous material may vary depending on the magnitude of the load applied to the material during measurement, it cannot be generalized, but is preferably 1.0×10 0 Ω·cm or less, more preferably 1.0×10 -1 Ω·cm or less.
[0079] Here, the relationship between the volume resistivity of a conductive porous material and the load (pressure) applied to the material was studied. Fig.12 Graph showing the results of measuring the volume resistivity of the conductive porous material while varying the pressure in the range of 0.1 MPa to 64 MPa. The sample for measuring the volume resistivity is the frozen gel of the graphene-cellulose composite prepared in Example 1 described later ( Fig.12 The “(a) Unfired” graph of the cryogel) and the conductive porous material obtained by firing the cryogel at 1000°C for 1 minute ( Fig.12 The graph of “(b) 1000°C sintering” of the cryogel and the conductive porous material obtained by sintering the cryogel at 2700°C for 1 minute ( Fig.12 (c) 2700℃ firing curve).
[0080] Since the graph (a) is an uncalcined cryogel, the cellulose in the cryogel is not graphitized. Therefore, in the pressure range of 10 MPa or less, the volume resistivity is 1.0×10 1 ~1.0×10 7 The range of Ω·cm.
[0081] In the graphs (b) and (c), the cellulose is graphitized by calcining the cryogel, and the volume resistivity decreases sharply. In the graph (b), the volume resistivity is 5.0×10 -2 ~1.0×10 0 Ω·cm. In the curve (c), in the same pressure range, the volume resistivity is 1.0×10 -3 ~1.0×10 -1 Ω·cm.
[0082] It should be noted that when a large load of 10 MPa or more is applied, the volume resistivity is substantially constant and almost saturated in any of the graphs (a) to (c). This is probably because the pores inside the conductive porous material collapse.
[0083] Therefore, by measuring the range of volume resistivity in the range of 10 MPa or less in which the volume resistivity varies with pressure, the range of volume resistivity of the conductive porous material to be measured can be roughly known.
[0084] The conductive porous material of one embodiment of the present invention has a volume resistivity of 1.0×10 -3 ~1.0×10 0 If the conductivity is within the range of Ω·cm, it can be said that the conductivity is suitable for electrode materials.
[0085] In the skeleton structure, preferably more than 80 atomic % of the entire skeleton structure is carbon atoms, and a conductive porous material with high conductivity can be obtained. The types and composition ratios of the elements constituting the skeleton structure can be known by elemental analysis (EA: Elemental Analysis). In elemental analysis, combustion method (destructive analysis) and X-ray photoelectron spectroscopy (XPS: X-ray photoelectron Spetroscopy, non-destructive analysis) are known. In the above-mentioned combustion method, the amount of water, carbon dioxide, nitrogen dioxide, etc. produced by completely burning the sample is evaluated, thereby obtaining the ratio of carbon, hydrogen, nitrogen, etc. contained in the sample. In the above-mentioned X-ray photoelectron spectroscopy, X-rays are irradiated to the sample surface, and the kinetic energy of the photoelectrons released from the sample surface is measured, thereby analyzing the types and chemical bonding states of the elements constituting the surface. By using such a method, the ratio of carbon atoms in the skeleton structure can be calculated.
[0086] Preferably, the skeleton structure comprises a calcined product obtained by calcining one or more fibrous carbon sources selected from the group consisting of cellulose, chitin, chitosan, lignin, and tannic acid. 14 By combining information from C measurement and elemental analysis with morphological histology using an optical microscope or an electron microscope, it is possible to determine whether the fibrous carbon source is of biological origin and thus the type of the fibrous carbon source.
[0087] (Pore characteristics of conductive porous materials)
[0088] The specific surface area of the conductive porous material is preferably 40 to 3000 m 2 / g, more preferably 100 to 3000 m 2 / g.
[0089] The specific surface area of the conductive porous material is determined by N2 gas adsorption measurement based on JIS Z 8830: 2013. Specifically, the amount of N2 gas required to form a monomolecular layer (= specific surface area) is calculated by performing BET curve analysis on the desorption side of the N2 gas adsorption-desorption isotherm.
[0090] The average pore diameter distribution of the conductive porous material is preferably mesopores (2 to 200 nm), but may also have macropores larger than 200 nm.
[0091] The average pore diameter distribution of the conductive porous material is also obtained by N 2 gas adsorption measurement based on JIS Z 8830:2013, and specifically, is calculated based on the BJH analysis of the N 2 gas adsorption-desorption isotherm.
[0092] (Volume density of conductive porous materials)
[0093] The bulk density of the conductive porous material is preferably 50 to 500 kg / m 3 range.
[0094] If the volume density of the conductive porous material is 50 kg / m 3 If the volume density is 500 kg / m 3 Below this, since the spatial volume of the material is fully contained, the specific surface area is large, the number of adsorbed ions becomes relatively large, and the capacitance becomes large.
[0095] It should be noted that the bulk density of the conductive porous material is usually different from the bulk density of the conductive porous material in other forms (e.g., the state of being crushed, coated, and dried to form a membrane electrode). The bulk density can be measured based on JIS Z 2504:2020 (apparent density) or JIS Z 2512:2012 (tapped density).
[0096] The skeleton structure containing fibrous carbon has a spider web-like three-dimensional network structure. In the conductive porous material, graphene is evenly distributed throughout the skeleton structure, and graphene and fibrous carbon are finely composited. Since the graphene is held by the skeleton structure, the mutual aggregation of graphene is suppressed.
[0097] <Electrode comprising a conductive porous material>
[0098] The electrode of this embodiment includes the above-mentioned conductive porous material.
[0099] In the conductive porous material of the embodiment, the spider web-like skeleton structure containing fibrous carbon is composited with graphene without aggregation, and the specific surface area is large. Therefore, the conductive porous material of the present invention is suitable for a wide range of uses, such as electrodes of power storage devices such as lithium ion secondary batteries and double-layer capacitors, and power generation devices such as fuel cells and solar cells.
[0100] <Method for producing conductive porous material>
[0101] In reference Figure 1A to Figure 1D The method for manufacturing the conductive porous material 115 of this embodiment will be described below. The method for manufacturing the conductive porous material 115 includes steps (1) to (3).
[0102] (1) Preparation process of dispersion 108:
[0103] The dispersion medium 102 , the graphene source 101 , and the biogenic fibrous carbon source 105 are mixed, and external energy is applied to prepare a dispersion liquid 108 containing the dispersion medium 102 , the graphene 106 , and the fibrous carbon source 105 .
[0104] (2) Production process of composite 113:
[0105] The dispersion medium 102 is removed from the dispersion liquid 108 to produce a composite 113 including the graphene 106 and the fibrous carbon source 105 .
[0106] (3) Firing process of composite 113:
[0107] The composite 113 is fired to obtain a conductive porous material 115 including a skeleton structure 107 made of biogenic fibrous carbon and graphene 106 held by the skeleton structure 107 .
[0108] Each process is described in detail below.
[0109] (1) Preparation process of dispersion 108:
[0110] Figure 1A 1 is a schematic diagram showing a state where a graphene source 101 is added to a dispersion medium 102. The graphene source 101 includes a plurality of graphenes 106. Inside the graphene source 101, the plurality of graphenes 106 are aggregated in a mutually stacked state, for example. Figure 1A In the state shown without the fibrous carbon source 105 , even if the graphene 106 is forcibly peeled off, the graphene 106 will re-aggregate and settle in the dispersion medium 102 once left because the dispersibility of the graphene 106 in the dispersion medium 102 is insufficient.
[0111] Furthermore, even if a dispersion is prepared from graphite as the graphene source 101 and water as the dispersion medium 102 , graphite is highly hydrophobic and therefore graphite and water are not sufficiently mixed, and graphite exfoliation itself does not proceed efficiently.
[0112] In contrast, in process (1), if Figure 1B As shown, a dispersion medium 102, a graphene source 101 and a fibrous carbon source 105 of biological origin are mixed, and external energy is given to the mixture. Thus, the graphene source 101 is physically peeled off and separated into a plurality of graphenes 106. Since the graphene 106 is attached to the fibrous carbon source 105, re-agglomeration is hindered. It can be inferred that the mechanism is because the graphene 106 and the negatively charged fibrous carbon source 105 undergo electrostatic interaction, thereby performing composite at the molecular level. In the dispersion 108, since the graphene 106 can maintain a dispersed state, it can be said that the dispersion 108 has excellent dispersibility. The dispersion shows high dispersibility, and there is no situation of graphene sedimentation even if it is left to stand for a long time.
[0113] The biogenic fibrous carbon source 105 is sometimes referred to as a “biomass dispersant” because it is a biogenic resource capable of holding the graphene 106 in a dispersed state.
[0114] The mixing order of the dispersion medium 102, the graphene source 101 and the bio-derived fibrous carbon source 105 is arbitrary. For example, a fibrous carbon source slurry in which the fibrous carbon source 105 is mixed in a small amount of the dispersion medium 102 and a graphene source mixed liquid in which the graphene source 101 is mixed in the remaining dispersion medium 102 can be prepared separately, and then the fibrous carbon source slurry is added to the graphene source mixed liquid.
[0115] As a device for imparting external energy, a water jet, microwave, ultrasonic wave, etc. are suitable. The water jet can be appropriately used in various shapes of chambers such as a ball collision chamber, an oblique collision chamber, a single nozzle chamber, etc., and the treatment can be performed at a high pressure of, for example, 100 to 245 MPa, preferably 200 to 245 MPa. The number of treatments can be 1 to 20 times, preferably 5 to 10 times.
[0116] By applying external energy, the graphene source 101 is physically exfoliated to produce the graphene 106 , and thus the process of applying external energy is sometimes referred to as “exfoliation process”.
[0117] In this manner, the dispersion liquid 108 (graphene-biomass dispersion liquid) containing the dispersion medium 102 , the graphene 106 , and the fibrous carbon source 105 is prepared.
[0118] As the dispersion medium 102 , a known dispersion medium such as an organic solvent or an ionic liquid can be used. However, from the viewpoints of economic efficiency, environmental compatibility, and safety assurance, it is preferable to use water as the dispersion medium.
[0119] The graphene source 101 may be any raw material that generates graphene 106 by interlayer exfoliation. The graphene source 101 is preferably one or more selected from artificial graphite, natural graphite, and multilayer graphene. The shape and form of the graphite (artificial graphite and natural graphite) are not particularly limited, and known graphites such as flaky graphite, scaly graphite, earthy graphite, expanded graphite, and spherical graphite can be used.
[0120] It should be noted that when a water jet is used as the external energy source, from the viewpoint of preventing clogging of the piping, it is preferred to use a graphene source 101 having a filler diameter smaller than the piping diameter of the water jet. For example, when the piping diameter is 100 μm, the filler diameter of the graphene source 101 is preferably 50 μm or less.
[0121] As the biologically derived fibrous carbon source (biomass dispersant) 105, a substance having a degree of polymerization of 200 to 800 and having a hydroxyl group on the surface is preferred. In addition, a substance that can form a skeleton structure 107 with a carbon atom content of 80 atomic % or more after being calcined in step (c) is preferred. Specifically, the fibrous carbon source 105 is preferably one or more selected from cellulose, chitin, chitosan, lignin, and tannic acid.
[0122] The fibrous carbon source 105 captures the separated graphene 106 and suppresses reaggregation, so it is preferred that the specific surface area of the fibrous carbon source 105 is large. From the viewpoint of increasing the specific surface area, the primary fiber diameter of the fibrous carbon source 105 is preferably 100 nm or less. The fibrous carbon source 105 can be used appropriately with a fiber length ranging from short (e.g., 1 μm) to extremely long (e.g., 50 μm).
[0123] (2) Production process of composite 113:
[0124] The dispersion medium 102 is removed from the dispersion 108 prepared in step (1) (i.e., dried) to obtain a composite 113 (graphene-biomass composite) including graphene 106 and a fibrous carbon source (biomass dispersant) 105. The graphene-biomass composite 113 may be in a state where the graphene 106 is evenly distributed in a spider web-like three-dimensional structure composed of the fibrous carbon source 105.
[0125] It should be noted that the composite 113 may be in a gel state, and the composite 113 in this state is sometimes referred to as a "graphene-biomass composite gel".
[0126] As a method for removing the dispersion medium 102, known drying methods such as supercritical drying, freeze drying, atmospheric pressure drying, and vacuum drying can be used. In view of productivity and economy, freeze drying is preferred. Freeze drying can suppress the shrinkage caused by capillary force when the dispersion medium 102 is removed and dried from the dispersion 108. Therefore, it is easy to form a graphene-biomass composite 113 in which graphene 106 is evenly distributed in a spider web-like three-dimensional structure composed of a fibrous carbon source 105.
[0127] By freeze drying, a frozen gel (graphene-biomass composite gel 113) is obtained from the dispersion medium 102. The freeze drying may be performed at, for example, -50°C to 0°C, preferably -50°C to -20°C, and under a reduced pressure of 100 Pa or less, and further 1 Pa or less.
[0128] (3) Firing process of composite 113:
[0129] The composite 113 is fired to obtain a conductive porous material 115. The purpose of this step is to burn off the foreign elements (hydrogen, oxygen, nitrogen, etc.) other than carbon contained in the biologically derived fibrous carbon source (biomass dispersant) 105, and promote the reconstruction and graphitization (aromatization) of the carbon skeleton. By firing the fibrous carbon source 105 at a high temperature to form carbon fibers, the spider web-like skeleton structure 107 can be made conductive.
[0130] The calcination conditions are as follows: in an inert gas atmosphere, at a calcination temperature of 2000 to 2700° C., preferably 2500 to 2700° C. The calcination time is 1 to 300 minutes, preferably 60 to 240 minutes. The heating rate to the calcination temperature is 1 to 20° C. / min, preferably 5 to 15° C. / min.
[0131] <Raw material amount>
[0132] In the step (1) of preparing the dispersion 108 , in order to obtain a dispersion 108 having particularly excellent dispersibility, preferred blending amounts of the respective components are described.
[0133] The blending amount of the graphene source 101 is preferably 0.1 to 2.0 parts by weight, more preferably 0.25 to 1.0 parts by weight, relative to the total weight of the dispersion 108 , so that the dispersion 108 in which the graphene 106 is uniformly dispersed can be produced.
[0134] It is preferred that a small amount of the dispersion medium 102 be separated from the bio-derived fibrous carbon source 105, the fibrous carbon source 105 be mixed therein to form a slurry, and then the fibrous carbon source slurry (biomass dispersant slurry) is added to the remaining dispersion medium 102 together with the graphene source 101. The amount of the fibrous carbon source slurry is adjusted by the concentration of the fibrous carbon source 105 in the fibrous carbon source slurry (sometimes referred to as "biomass concentration"), the type and amount of the graphene source 101. For example, when the biomass concentration of the fibrous carbon source slurry is 2.0%, the dispersion 108 in which the fibrous carbon source 105 is uniformly dispersed can be prepared by 1.0 to 50.0 parts by weight, preferably 5.0 to 30.0 parts by weight, relative to the total weight of the dispersion 108.
[0135] As an example, when 10 parts by weight of a fibrous carbon source slurry having a biomass concentration of 2.0% is added to a mixed solution of 89 g of a dispersion medium and 1 g of a fibrous carbon source, 0.02 g of the fibrous carbon source 105 is present in 100 g of the total weight of the dispersion 108. In terms of mass ratio, the graphene source: fibrous carbon source = 50:1, and the substantial amount of the fibrous carbon source 105 is very small relative to the amount of the graphene source 101.
[0136] According to the method for producing a conductive porous material according to an embodiment of the present invention, the aggregation of graphene can be suppressed in a dispersion without performing oxidation treatment of graphene by using a biogenic fibrous carbon source 105. Thus, a conductive porous material having a large specific surface area can be produced safely and at low cost.
[0137] Example
[0138] Embodiments of the present invention will be described based on examples. However, embodiments of the present invention are not limited to the following examples.
[0139] <Example 1>
[0140] A measurement sample of the conductive porous material was prepared under the following conditions.
[0141] Dispersion medium: water (ultrapure water)
[0142] Graphene source: Artificial graphite with a filler diameter of less than 20 μm (manufactured by Panasonic, PGF)
[0143] ・Biogenic fibrous carbon source: cellulose nanofiber (Sugino Machine Co., Ltd., WF0-10002)
[0144] The cellulose nanofibers were prepared in advance into a slurry with a biomass concentration of 2 wt%.
[0145] In a 200ml bottle with a lid, 79g of weighed water and 1g of artificial graphite powder were mixed, and 20g of cellulose nanofiber slurry was further added and the lid was closed. Afterwards, the bottle was fully shaken by hand to stir the water, artificial graphite and slurry in the bottle to prepare a mixed solution. Then, 100g of the obtained mixed solution was subjected to a stripping treatment (ball collision chamber, pressure: 245MPa, number of passes: 10) using a water jet (manufactured by SUGINO MACHINE). Thus, a dispersion in which graphene and cellulose nanofibers were uniformly dispersed was obtained. The stripping treatment was performed for about 10 minutes to obtain about 80g of a graphene-biomass dispersion.
[0146] The obtained graphene-biomass dispersion was freeze-dried (-20°C, 100Pa) to obtain a bulk composite (cryogel). The composite was subjected to high-temperature treatment in a calcining furnace (heating rate: 10°C min -1 , treatment temperature: 2700° C., treatment time: 1 minute), thereby obtaining a sintered body (conductive porous material). Figure 2 FIG. 2 shows a photograph of the appearance of the sintered body (conductive porous material) obtained in Example 1. Figure 3 The SEM image of the conductive porous material is shown in FIG. Figure 3 As shown in FIG. 1 , the conductive porous material is a porous material in which graphene is held in a fibrous carbon skeleton structure (a spider web-like three-dimensional network structure). Graphene is attached to the entire skeleton structure.
[0147] Determination of specific surface area of conductive porous materials
[0148] The specific surface area of the conductive porous material was determined by N2 gas adsorption measurement based on JIS Z 8830:2013. The specific surface area of the sintered body was 99 m 2 / g, confirmed that the PGF (specific surface area: 11m 2 / g), the specific surface area increased by 9 times.
[0149] ·Determination of volume resistivity of conductive porous materials
[0150] About 1g of the conductive porous material is weighed using an electronic balance and added to the cylindrical probe assembly of the automatic powder resistance measurement system (manufactured by Nitto Seiko Analytical Technology Co., Ltd., MCP-PD600). The powder sample is laid on the bottom surface of the probe assembly in a manner that makes the thickness of the powder sample uniform to a certain extent. The probe assembly with the powder sample added is placed, and while pressure is automatically applied to the powder sample in the thickness direction, the volume resistivity in the thickness direction is measured. The measurement is performed in the pressure range of 0MPa (unpressurized) to 63MPa. The volume resistivity in the range of 0MPa (unpressurized) to 10MPa is 1.0×10 0 Ω·cm or less.
[0151] Determination of biomass content of conductive porous materials based on accelerator mass spectrometry (AMS)
[0152] The sample is burned, and the generated carbon dioxide is reduced with hydrogen using an iron catalyst to generate graphite. The graphite is filled into a cathode with an inner diameter of 1 mm using a hand press, and then inserted into a disk (Japanese: ホイール) and installed in the AMS measurement device. 14 C-AMS dedicated device (NEC), 14 The count of C, 13 C concentration ( 13 C / 12 C) 14 C concentration ( 14 C / 12 C). At this time, oxalic acid was used as a standard sample. The biomass degree was calculated using pMC corrected according to ASTM D6866-22 for the measured value. The biomass degree of the conductive porous material was 17 pMC.
[0153] Fig.13 The relationship between the weight ratio of cellulose nanofibers in the conductive porous material (before calcination) and the biomass degree of the conductive porous material (calcined body) is shown in FIG. Here, the "weight ratio of cellulose nanofibers" refers to the weight ratio of cellulose nanofibers in the raw material, and more specifically, the weight ratio of cellulose nanofibers before calcination when the total weight of artificial graphite and cellulose nanofibers before calcination is set to 100wt%.
[0154] For reference, artificial graphite (PGF, manufactured by Panasonic) with a filler diameter of less than 20 μm as a graphene source and cellulose nanofibers (WF0-10002, manufactured by SUGINOMACHINE) as a fibrous carbon source derived from biomass were measured by AMS. 13C concentration, and the biomass degree is calculated. It should be noted that unfired artificial graphite and unfired cellulose nanofibers were used in the measurement. The results of the measurement showed that the biomass degree of petroleum-derived artificial graphite (cellulose nanofiber weight ratio: 0wt%) was 0pMC, and the biomass degree of cellulose nanofiber (cellulose nanofiber weight ratio: 100wt%) was 100pMC.
[0155] <Example 2>
[0156] A conductive porous material was prepared by the same procedure and conditions as in Example 1 except that the amount of water added was changed to 89 g and the amount of the cellulose nanofiber slurry added was changed to 10 g.
[0157] Figure 4 The SEM image of the conductive porous material is shown in FIG. Figure 4 As shown in FIG. 1 , the conductive porous material is a porous material in which graphene is held in a fibrous carbon skeleton structure (a spider web-like three-dimensional network structure). Graphene is attached to the entire skeleton structure.
[0158] By the same procedure as in Example 1, the specific surface area, volume resistivity and biomass content of the conductive porous material were measured.
[0159] The specific surface area of the conductive porous material is 105m 2 / g, confirmed that the PGF (specific surface area: 11m 2 / g), the specific surface area increased by about 10 times.
[0160] The volume resistivity of the conductive porous material in the range of 0 MPa (unpressurized) to 10 MPa is 1.0×10 0 Ω·cm or less.
[0161] The biomass degree of the conductive porous material is 9.5 pMC. The biomass degree results are shown in Fig.13 middle.
[0162] <Example 3>
[0163] A conductive porous material was produced by the same procedure and conditions as in Example 1, except that the graphene source was changed from artificial graphite to natural graphite (CGB-12R, manufactured by Nippon Graphite Co., Ltd.).
[0164] Figure 5 The SEM image of the conductive porous material is shown in FIG. Figure 5 As shown in FIG. 1 , the conductive porous material is a porous material in which graphene is held in a fibrous carbon skeleton structure (a spider web-like three-dimensional network structure). Graphene is attached to the entire skeleton structure.
[0165] By the same procedure as in Example 1, the specific surface area and volume resistivity of the conductive porous material were measured.
[0166] The specific surface area of the conductive porous material is 99m 2 / g, and confirmed that the CGB-12R (specific surface area: 8m 2 / g), the specific surface area increased by about 12 times.
[0167] The volume resistivity of the conductive porous material in the range of 0 MPa (unpressurized) to 10 MPa is 1.0×10 0 Ω·cm or less.
[0168] <Example 4>
[0169] A conductive porous material was produced by the same procedure and conditions as in Example 1, except that the graphene source was changed from artificial graphite to multilayer graphene (Gi-PW-F031, manufactured by Ishihara Chemical Co., Ltd.).
[0170] Figure 6 The SEM image of the conductive porous material is shown in FIG. Figure 6 As shown in FIG. 1 , the conductive porous material is a porous material in which graphene is held in a fibrous carbon skeleton structure (a spider web-like three-dimensional network structure). Graphene is attached to the entire skeleton structure.
[0171] By the same procedure as in Example 1, the specific surface area and volume resistivity of the conductive porous material were measured.
[0172] The specific surface area of the conductive porous material is 44m 2 / g, confirmed that the Gi-PW-F031 (specific surface area: 29m 2 / g), the specific surface area increased by about 1.5 times.
[0173] The volume resistivity of the conductive porous material in the range of 0 MPa (unpressurized) to 10 MPa is 1.0×10 0 Ω·cm or less.
[0174] <Example 5>
[0175] A conductive porous material was produced by the same procedure and conditions as in Example 1, except that the graphene source was changed from artificial graphite to single-layer graphene (N002-PDR, manufactured by Ishihara Chemical Co., Ltd.).
[0176] Figure 7 The SEM image of the conductive porous material is shown in FIG. Figure 7As shown in FIG. 1 , the conductive porous material is a porous material in which graphene is held in a fibrous carbon skeleton structure (a spider web-like three-dimensional network structure). Graphene is attached to the entire skeleton structure.
[0177] By the same procedure as in Example 1, the specific surface area and volume resistivity of the conductive porous material were measured.
[0178] The specific surface area of the conductive porous material is 278m 2 / g, confirmed that the N002-PDR (specific surface area: 423m 2 / g), a decrease in specific surface area was observed, but a high specific surface area was maintained.
[0179] The volume resistivity of the conductive porous material in the range of 0 MPa (unpressurized) to 10 MPa is 1.0×10 0 Ω·cm or less.
[0180] <Example 6>
[0181] A conductive porous material was prepared by the same procedure and conditions as in Example 1, except that the biogenic fibrous carbon source was changed from cellulose nanofibers to chitin nanofibers (SF0-20002, manufactured by SUGINOMACHINE).
[0182] Figure 8 The SEM image of the conductive porous material is shown in FIG. Figure 8 As shown in FIG. 1 , the conductive porous material is a porous material in which graphene is held in a fibrous carbon skeleton structure (a spider web-like three-dimensional network structure). Graphene is attached to the entire skeleton structure.
[0183] By the same procedure as in Example 1, the specific surface area and volume resistivity of the conductive porous material were measured.
[0184] The specific surface area of the conductive porous material is 50m 2 / g, confirmed that the PGF (specific surface area: 11m 2 / g), the specific surface area increased by about 5 times.
[0185] The volume resistivity of the conductive porous material in the range of 0 MPa (unpressurized) to 10 MPa is 1.0×10 0 Ω·cm or less.
[0186] <Example 7>
[0187] A conductive porous material was prepared by the same procedure and conditions as in Example 1, except that the biogenic fibrous carbon source was changed from cellulose nanofiber to chitosan nanofiber (EF0-20002, manufactured by SUGINOMACHINE).
[0188] Fig. 9 The SEM image of the conductive porous material is shown in FIG. Fig. 9 As shown in FIG. 1 , the conductive porous material is a porous material in which graphene is held in a fibrous carbon skeleton structure (a spider web-like three-dimensional network structure). Graphene is attached to the entire skeleton structure.
[0189] By the same procedure as in Example 1, the specific surface area and volume resistivity of the conductive porous material were measured.
[0190] The specific surface area of the conductive porous material is 126m 2 / g, confirmed that the PGF (specific surface area: 11m 2 / g), the specific surface area increased by about 10 times.
[0191] The volume resistivity of the conductive porous material in the range of 0 MPa (unpressurized) to 10 MPa is 1.0×10 0 Ω·cm or less.
[0192] <Comparative Example 1>
[0193] A graphene-biomass dispersion was obtained by the same procedure and conditions as in Example 1 except that the amount of water added was changed to 98 g and the amount of the cellulose nanofiber slurry added was changed to 1 g.
[0194] The graphene-biomass dispersion was left for one day, and the graphene precipitated and phase-separated. The precipitated graphene was freeze-dried (-20°C, 100Pa) to obtain a bulk composite (cryogel). The composite was calcined using the same steps and conditions as in Example 1 to obtain a calcined body. Fig.10 FIG. 2 shows a photograph of the appearance of the sintered body obtained in Comparative Example 1. Fig.11 The SEM image of the sintered body is shown in FIG. Fig.11 As shown, a fibrous carbon skeleton structure is not formed in the fired body, and graphene is in an aggregated state where graphene is stacked on top of each other.
[0195] By the same procedure as in Example 1, the specific surface area, volume resistivity and biomass content of the conductive porous material were measured.
[0196] The specific surface area of the conductive porous material is 11m 2 / g, confirmed that the PGF (specific surface area: 11m 2 / g) are equivalent.
[0197] The volume resistivity of the conductive porous material in the range of 0 MPa (unpressurized) to 10 MPa is 1.0×10 0 Ω·cm or less.
[0198] The biomass of the conductive porous material is only 1 pMC. The biomass results are shown in Fig.13 middle.
[0199] according to Fig.13 The results of Examples 1 and 2 and Comparative Example 1 indicate that the conductive porous material having biogenic fibrous carbon is preferable within the range of a biomass degree of 5 to 55 pMC.
[0200] Industrial Applicability
[0201] According to the method for producing a conductive porous material of one embodiment of the present invention, by using a fibrous carbon source of biological origin, the aggregation of graphene in the dispersion can be suppressed without performing an oxidation treatment of a graphene source (graphite, etc.), thereby obtaining a dispersion with excellent dispersibility. Therefore, the production efficiency of the conductive porous material of the production method of the present invention is high, and it also has high utilization value in industry.
[0202] By using a manufacturing method in one embodiment of the present invention, a conductive porous material can be obtained by finely compounding a spider web-like skeleton structure formed by carbon fibers with graphene. Such a conductive porous material can be used for a wide range of purposes, for example, it can be used as an electrode material for power storage devices such as lithium-ion secondary batteries and double-layer capacitors, and power generation devices such as fuel cells and solar cells.
[0203] Description of Reference Numerals
[0204] 101 Graphene source, 102 Dispersion medium, 105 Bio-derived fibrous carbon source, 106 Graphene, 107 Bio-derived fibrous carbonaceous skeleton structure, 108 Graphene-biomass dispersion, 113 Graphene-biomass composite, 115 Conductive porous material.
Claims
1. A conductive porous material comprising a skeleton structure comprising fibrous carbon of biological origin and graphene held by the skeleton structure, The volume resistivity of the conductive porous material measured under a pressure of 10 MPa or less is 1.0×10 -3 Ω·cm~1.0×10 0 Ω·cm, The biomass content of the conductive porous material measured by accelerator mass spectrometry (AMS) is in the range of 5 pMC to 55 pMC.
2. The conductive porous material according to claim 1, wherein In the skeleton structure, 80 atomic % or more of the entire skeleton structure is carbon atoms.
3. The conductive porous material according to claim 1, wherein The skeleton structure includes a calcined product obtained by calcining one or more fibrous carbon sources selected from the group consisting of cellulose, chitin, chitosan, lignin, and tannic acid. 4 . An electrode comprising the conductive porous material according to claim 1 .
5. A method for manufacturing a conductive porous material, the method being a method for manufacturing the conductive porous material according to any one of claims 1 to 3, comprising: (1) a step of mixing a dispersion medium, a graphene source, and a biogenic fibrous carbon source and applying external energy to prepare a dispersion liquid containing the dispersion medium, the graphene, and the fibrous carbon source; (2) a step of removing the dispersion medium from the dispersion liquid to produce a composite body including graphene and the fibrous carbon source; and (3) A step of firing the composite to obtain a conductive porous material.
6. The method for producing a conductive porous material according to claim 5, wherein: The fibrous carbon source is one or more selected from the group consisting of cellulose, chitin, chitosan, lignin and tannic acid.
7. The method for producing a conductive porous material according to claim 5, wherein: The graphene source is one or more selected from artificial graphite, natural graphite and multilayer graphene.
8. The method for producing a conductive porous material according to claim 5, wherein: The dispersion medium is water.
